Curcumin prevents formation of polyglutamine aggregates by inhibiting Vps36, a component of the ESCRT-II complex. - Meenakshi Verma (Public Library of Science (PLoS), 2012)
Small molecules with antioxidative properties have been implicated in amyloid disorders. Curcumin is the active ingredient present in turmeric and known for several biological and medicinal effects. Adequate evidence substantiates the importance of curcumin in Alzheimer's disease and recent evidence suggests its role in Prion and Parkinson's disease. However, contradictory effects have been suggested for Huntington's disease. This difference provided a compelling reason to investigate the effect of curcumin on glutamine-rich (Q-rich) and non-glutamine-rich (non Q-rich) amyloid aggregates in the well established yeast model system. Curcumin significantly inhibited the formation of htt72Q-GFP (a Q-rich) and Het-s-GFP (a non Q-rich) aggregates in yeast. We show that curcumin prevents htt72Q-GFP aggregation by down regulating Vps36, a component of the ESCRT-II (Endosomal sorting complex required for transport). Moreover, curcumin disrupted the htt72Q-GFP aggregates that were pre-formed in yeast and cured the yeast prion, [PSI(+)].